2021
DOI: 10.3390/cells10030485
|View full text |Cite
|
Sign up to set email alerts
|

Importance of between and within Subject Variability in Extracellular Vesicle Abundance and Cargo when Performing Biomarker Analyses

Abstract: Small extracellular vesicles (sEV) have emerged as a potential rich source of biomarkers in human blood and present the intriguing potential for a ‘liquid biopsy’ to track disease and the effectiveness of interventions. Recently, we have further demonstrated the potential for EV derived biomarkers to account for variability in drug exposure. This study sought to evaluate the variability in abundance and cargo of global and liver-specific circulating sEV, within (diurnal) and between individuals in a cohort of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 38 publications
(53 reference statements)
0
28
1
Order By: Relevance
“…Prandial state has also been suggested to impact circulating EV (Witwer et al 2013). While this work demonstrated no effect of fasting on EV abundance, particle size and generic or liver specific markers (Newman et al 2021), others previously reported significant increases in fed compared to fasted samples (Mørk et al 2016). Differences may be attributed to EV isolation methods selected in these studies, as increased post-prandial lipoprotein levels can interfere with vesicle counting in less pure EV isolates.…”
Section: Pre-analytical Factorscontrasting
confidence: 51%
See 3 more Smart Citations
“…Prandial state has also been suggested to impact circulating EV (Witwer et al 2013). While this work demonstrated no effect of fasting on EV abundance, particle size and generic or liver specific markers (Newman et al 2021), others previously reported significant increases in fed compared to fasted samples (Mørk et al 2016). Differences may be attributed to EV isolation methods selected in these studies, as increased post-prandial lipoprotein levels can interfere with vesicle counting in less pure EV isolates.…”
Section: Pre-analytical Factorscontrasting
confidence: 51%
“…The time of day at which samples are collected should be kept constant to control for circadian variations (Théry et al 2018;Witwer et al 2013;Coumans et al 2017). By way of example, a recent report from our group showed that while no change in total abundance and size of EVs occurred from morning to afternoon, levels of generic EV marker, CD81, was decreased and the hepatocyte specific marker, ASGR1, was increased (Newman et al 2021). The potential for variability in molecular cargo should thus be accounted for in sampling protocols, particularly in the context of liver derived markers such as DMEs.…”
Section: Pre-analytical Factorsmentioning
confidence: 94%
See 2 more Smart Citations
“…107,108 Conversely, a potential disadvantage of investigating EVs as biomarkers relates to the complexities of EV interactions with target cells and their poorly understood biogenesis pathways. 5,23 In addition, recent studies have detected diurnal patterns of expression in EV markers 109 and variability in EV content within participants related to physiological activities, such as exercise and sample collection conditions. 110 More studies are needed to disentangle this variability (e.g., by estimating the ratio of sample EVs to total protein in the sample), and to establish thresholds for specific pathologic states.…”
Section: Ev Characterization and Biomarker Discoverymentioning
confidence: 99%